Upaya Meningkatkan Kemampuan Mengenal Huruf Berbantuan Media Kartu di TK Tunas Harapan Desa Sei Lambu Makmur Kecamatan Tapung - Andika Defita Sari; Afriza Rahma Rani; Mohammad Fauziddin (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study is motivated by the low letter recognition skills of students in group A at Tunas Harapan Kindergarten. This study aims to improve the letter recognition skills of group A students at Tunas Harapan Kindergarten through the use of card media. The type of research used was classroom action research with the research subjects being group A students at Tunas Harapan Kindergarten. Data collection techniques used observation and documentation. The results showed that the use of card media can improve the ability to know letters in group A students at Tunas Harapan Kindergarten. The results showed an increase in each cycle conducted. In the pre-action, the average score of students' letter skills was 4.21. In cycle I, meeting I experienced an increase in the average score of students' letter skills of 5.14 and at meeting II it increased to 6.28. Then in cycle II, the first meeting increased again to 7.28 and at the second meeting increased again to 9.14. Thus, it can be concluded that the application of card media can improve students' letter skills in group A of Tk Tunas Harapan. Keywords: Letter Recognition, Card Media, CAR